Improving Stock Availability Accuracy Using Min-Max Method for Material Requirement Planning (MRP) Item Bolt Set at PT Lion Metal Works - Silvi Istiqomah; Fatnika Fauziyah; Ade Fathur Noviandre Majid; Kamelia Salsabilla; Perdana Suteja (Universitas Muria Kudus, 2026)
PT Lion Metal Works faces frequent raw material shortages and surpluses, disrupting production and emphasizing the need for better inventory management. This study aims to improve stock accuracy for bolt set items using the Min-Max method. The research involved analyzing historical data and forecasting demand to establish reorder points and optimal inventory levels. Data collection techniques included historical data analysis and statistical demand forecasting. The implementation of the Min-Max method increased stock accuracy from 87% to 90%. Prior to this method, inventory management experienced frequent discrepancies and inefficiencies. Post-implementation, these issues were significantly reduced, resulting in more stable inventory levels. Key factors in this improvement included precise demand forecasting, efficient procurement lead time, and effective safety stock management. The study confirms the Min-Max method's effectiveness in optimizing inventory management, cutting costs, and ensuring smoother production. Benefits of the study include enhanced stock accuracy and minimized production disruptions. Recommendations for further improvement involve developing advanced information systems, regular employee training, and better supplier relationships.